2018
DOI: 10.2147/idr.s178831
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of rifampin, isoniazid, and ofloxacin resistance in Iranian isolates of <em>Mycobacterium tuberculosis</em> by high-resolution melting analysis

Abstract: BackgroundThe emergence of drug resistance among Mycobacterium tuberculosis (MTB) strains is a serious health concern worldwide. The development of rapid molecular diagnostic methods in recent years has a significant impact on the early detection of resistance to major anti-TB drugs in MTB isolates, which helps in employing appropriate treatment regimen and prevents the spread of drug-resistant strains. This study was designed to evaluate the efficacy of real-time PCR and high-resolution melting (HRM) curve an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Mutation analysis of drug resistance genes of second-line drugs showed that only gyrA gene of OFX resistance mutated in four second-line anti-tuberculosis drugs, and the mutation sites were 74, 90, 91 and 94. This is consistent with the results of Wang Z, Sirous M and others [35][36] .From the above analysis of drug resistance gene site we could see that there were not only the genetic and molecular biological characteristics of the mainstream MDR-TB strains at home and abroad, but also has a few special characteristics. These characteristics will provide a new idea for rapid detection of MDR-TB in Urumqi in the future.…”
Section: Discussionsupporting
confidence: 91%
“…Mutation analysis of drug resistance genes of second-line drugs showed that only gyrA gene of OFX resistance mutated in four second-line anti-tuberculosis drugs, and the mutation sites were 74, 90, 91 and 94. This is consistent with the results of Wang Z, Sirous M and others [35][36] .From the above analysis of drug resistance gene site we could see that there were not only the genetic and molecular biological characteristics of the mainstream MDR-TB strains at home and abroad, but also has a few special characteristics. These characteristics will provide a new idea for rapid detection of MDR-TB in Urumqi in the future.…”
Section: Discussionsupporting
confidence: 91%
“…However, based on our results, other advantages of an HRMA assay and real-time PCR technology are its ability to detect non-viable, fastidious, and unculturable organisms that would otherwise be missed by culture. Sirous et al, 42 in other bacterias, showed that HRMA assay is a rapid, accurate, and cost-effective method possessing high sensitivity and specificity for the determination of antibiotic resistance. However, A PCR-positive, culture-negative specimen may reflect a real pathogen, yet detecting them would lead to a biased lower sensitivity and specificity value of the HRMA test.…”
Section: Figurementioning
confidence: 99%
“…Out of the 509 potential studies, 52 studies met all inclusion criteria. (1, 759) A PRISMA flow diagram in Figure 1 illustrates the breakdown of number of articles excluded because of the specified criterion.…”
Section: Resultsmentioning
confidence: 99%